Successful usage of intravenous lipid emulsion in treatment of acute verapamil poisoning – A case report - Vuković Ercegović, Gordana N; Perković Vukčević, Nataša; Djordjević, Snežana; Šegrt, Zoran; Potrebić, Olivera; Janković, Snežana R; Jović Stošić, Jasmina; Marinković, Nadica (Vojnosanitetski pregled, 2017)
Introduction. During the last few years, intravenous lipid emulsions have been effectively used in treatment of acute poisonings with lipophilic substances, including verapamil. Case report. A 37-year-old women presented 1 hour after ingestion of 2.8 g verapamil with hypotension and complete heart block. Because of the applied standard therapy failure and further patients impairment, Intralipid® 20% was used. Sinus rhythm was restored, arterial blood pressure increased and verapamile concentrations, both total and free decreased. Conclusion. Intravenous lipid emulsion can be important in treatment of severe acute intoxication and cardiotoxicity caused by verapamil.